Audit of the first caesarean section in a reference hospital in the African environment - Zamané, Hyacinthe; Kain, Paul Dantola; Kiemtoré, Sibraogo; Dembelé, Adama; Ouédraogo, Jerome; Ouédraogo, Ali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background The practice of a first caesarean section can condition the future obstetric prognosis. The aim of this work was to study the indications of the first caesarean sections at the Yalgado Ouedraogo Teaching Hospital in Ouagadougou. Methods: This was a cross-sectional study with prospective collection. The data were collected from 1 March to 30 May 2018. The women who benefited from caesarean section for the first time were the study population. The review of the documents, the interview with the patients and the expert opinion were the techniques used. The expert opinion made it possible to determine whether or not the caesarean section was preventable. Results: The first caesarean sections accounted for 62.5% (280/448) of all caesarean sections and 34.6% (280/810) of all childbirths in the period. Caesarean section was urgently performed in 95% of cases. It was mostly an obstetrical indication. Probable fetal asphyxia was the first major indication (27.5%) followed by preeclampsia/eclampsia (15.7%) and uterine pre-rupture syndrome (8.9%). Caesarean section was found to be avoidable in 53 cases (18.9%). Probable fetal asphyxia was the most common indication (22.4%) of these preventable caesarean sections. Conclusions: The good management of preeclampsia, the strengthening of the birth room in fetal and maternal monitoring equipment, the close coaching of physicians in specialization and the periodic audits of practices would reduce the preventable caesarean sections.